Aktualisasi Pemberdayaan Keluarga Dalam Pemberantasan Penyalahgunaan Narkoba - Abd. Hamid Isa; Mohamad Zubaidi; Zulkarnain Anu (Universitas Negeri Gorontalo, 2023)
The phenomenon of abuse of narcotics and illegal drugs among the younger generation is currently increasing. The condition of deviant behavior of the younger generation can endanger the survival of our nation's development because they are increasingly fragile and devoured by addictive substances that destroy nerves. Our young generation can no longer think clearly, as a result, the assets of this strong and intelligent nation will only be a memory. The family as a micro community in society has an important role in controlling and eradicating the dangers of drugs. Actualizing the function of the family as a forum for empowerment is one of the pillars that needs to be done and therefore family resilience is the basic foundation of the strength of the sustainability of national development. The Thematic Community Service Program by LPPM UNG in 2021 is oriented to assisting the community in combating drug abuse which is currently rife in society in general. The programs that will be delivered by students will refer to assistance activities to the community to be equally resilient and responsive in eradicating drug abuse. The target of the theme is